2023
DOI: 10.1021/acs.est.3c01121
|View full text |Cite
|
Sign up to set email alerts
|

Toward Multiscale Measurement-Informed Methane Inventories: Reconciling Bottom-Up Site-Level Inventories with Top-Down Measurements Using Continuous Monitoring Systems

Abstract: Government policies and corporate strategies aimed at reducing methane emissions from the oil and gas sector increasingly rely on measurement-informed, site-level emission inventories, as conventional bottom-up inventories poorly capture temporal variability and the heavy-tailed nature of methane emissions. This work is based on an 11-month methane measurement campaign at oil and gas production sites. We find that operator-level top-down methane measurements are lower during the end-of-project phase than durin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In addition, new solutions such as surveys using aerial systems, drones, satellites, and fixed continuous monitoring systems promise faster and more cost-effective emission reductions. Successful deployment of these technologies across the oil and gas supply chain over the past decade has demonstrated the potential for their use in regulatory LDAR programs. These technologies have also been extensively evaluated through controlled release tests to identify key performance parameters such as probability of detection curves, false positivity rate, and quantification accuracy. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, new solutions such as surveys using aerial systems, drones, satellites, and fixed continuous monitoring systems promise faster and more cost-effective emission reductions. Successful deployment of these technologies across the oil and gas supply chain over the past decade has demonstrated the potential for their use in regulatory LDAR programs. These technologies have also been extensively evaluated through controlled release tests to identify key performance parameters such as probability of detection curves, false positivity rate, and quantification accuracy. …”
Section: Introductionmentioning
confidence: 99%
“…The emissions distribution for general and tank fugitives were based on a compilation of bottom-up measurement studies, while the large emitter distribution was based on a recent aerial survey of the Permian basin. ,, While the EPA’s modeling was based on data that were available at that time, it raises two concerns. One, recent studies have shown that bottom-up emission inventories routinely underestimate emissions compared to top-down measurements. , Two, recent work that deployed both bottom-up and top-down technologies for leak detection showed that an OGI-based LDAR survey is likely to miss certain large emitter events such as those from tanks . Whether the effectiveness of alternative technologies in reducing methane emissions depends on the emission size distribution in the equivalence modeling has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Other relevant studies have also explored the variability of methane emission estimation methodologies. For instance, Daniels et al conducted research that utilized multi-scale technologies in the production segment and discovered substantial discrepancies in TD methods, with variations spanning over three orders of magnitude [25,26]. Similarly, Stokes et al [27] deployed two distinct aircraft-based emission measurement systems at tank battery sites and observed discrepancies in their respective estimates of total emissions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, emission event durations established using continuously operating ground methane monitors, or other relevant parametric process data, could be integrated with engineering calculations or emission quantification measurements made using aircraft overflights. 13 Measurements of total production basin emissions that sum emissions over thousands of sites and measurement of multiple co-emitted species could also be used to place constraints on extrapolation of individual site level measurements. 14 These are just a few of a wide variety of measurement integration methods that could be used to reduce uncertainties in methane emission estimates.…”
mentioning
confidence: 99%
“…The potentially large uncertainties in individual emission measurements and methods could be significantly reduced by integrating and reconciling measurements and engineering calculations made at multiple spatial and temporal scales. For example, emission event durations established using continuously operating ground methane monitors, or other relevant parametric process data, could be integrated with engineering calculations or emission quantification measurements made using aircraft overflights . Measurements of total production basin emissions that sum emissions over thousands of sites and measurement of multiple co-emitted species could also be used to place constraints on extrapolation of individual site level measurements .…”
mentioning
confidence: 99%